2022
DOI: 10.1002/ps.7322
|View full text |Cite
|
Sign up to set email alerts
|

AdsRNAdelivery system based on the rosin‐modified polyethylene glycol and chitosan induces gene silencing and mortality inNilaparvata lugens

Abstract: BACKGROUND: RNA interference (RNAi) technology has been considered as a promising pest control strategy due to its species selectivity. One of the popular RNAs is exogenous double strand RNA (dsRNA). However, dsRNA is easily degraded by nucleases and is difficult to pass through the insect body walls, and these factors restrict the application of RNAi technology in pest management. Here, the brown planthopper (BPH, Nilaparvata lugens), a major hemipteran pest of rice in Asia countries was used as a model insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…68 APG is known for its ecofriendly, nontoxic and mild non-ionic surfactant characteristics, typically blended with other surfactants to improve their permeability. 69 Additionally, APG can expedite the cellular uptake of nanoformulations by enhancing the flow of biofilm and promoting endocytosis of cell membranes. 70,71 Our formulation, comprising dsRNA/LDH/APG nanostructures, is designed to enhance RNAi effects.…”
Section: Discussionmentioning
confidence: 99%
“…68 APG is known for its ecofriendly, nontoxic and mild non-ionic surfactant characteristics, typically blended with other surfactants to improve their permeability. 69 Additionally, APG can expedite the cellular uptake of nanoformulations by enhancing the flow of biofilm and promoting endocytosis of cell membranes. 70,71 Our formulation, comprising dsRNA/LDH/APG nanostructures, is designed to enhance RNAi effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was successfully used for dsRNA insecticide-based approaches in mosquitoes and other insects [68][69][70][71], their nonspeci c impact on untargeted species should then be regarded when evaluating the e ciency of such method.…”
Section: Provisioning Methods Can Collaterally Impact Gene Expressionmentioning
confidence: 99%
“…Additionally, RCNPs were stable for 5 days on leaf surfaces, effectively protected from nuclease degradation and insect gut pH, and efficiently knocked down the targeted genes (JHAMT and AChE), resulting in 100% insect mortality, whereas the nontargeted insects like Spodoptera litura and Drosophila melanogaster were unaffected and showed no signs of toxicity (Kolge et al, 2021(Kolge et al, , 2023. A recent study demonstrated that topically applying dsRNAcoated with rosin-modified PEG and chitosan (dsRNA/ROPE@C) to Nilaparvata lugens (Brown plant hopper) causes excellent gene knockdown and mortality (Lyu et al, 2023). Recently, our team created chitosan-dsRNA nanopesticides, fed them to bollworms (Earias vittella), and observed considerable target gene knockdown and mortality (Sandal et al, 2023).…”
Section: Rnai-chitosan Biopesticides: Current Statusmentioning
confidence: 99%